Latest Developments in Officers’ Duties of SMEs - Adams , Michael (Journal of Law and Governance, 2011)
This paper examines the balance between officers' and directors' duties in the context of modern regulatory reform. The onus that falls on all directors, from a legal point of view, is applied irrespective of the size and complexity of the corporation. Thus, a small (micro-business) with a single director has the same legal obligation under the common law, the equitable fiduciary duties and the statutory obligations under the Corporations Act as Australia's largest entity, BHP Billiton. The current Federal Government is attempting to reduce the burden of red tape on business to help the economy. The regulators, in particular ASIC, are pursuing cases to enforce the law and increase compliance. There has been recent case law which helps explain the key statutory provisions and the underlying complexity of the law. The major defence and protection for officers' duties, is the so called “business judgement rule,” but it does not seem to be very effective and good quality insurance cover is probably much more useful in the commercial world.